An Analysis of Big Five Personality (OCEAN) in William Shakespeare’s Drama “Othello” - Saralena Manik; Yeni Adventry Tanjung; Christy Aulia Dunov Simanjuntak; Jovan Morientes Nigel; Syamsul Bahri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
Human personality is diverse and influences the way people act, think, and interact in daily life. These differences also appear in literature, especially in drama, where characters reveal their traits through dialogue, actions, and conflicts. This study aims to analyze the personality of Othello in William Shakespeare’s Othello using the Big Five Personality Traits (OCEAN). This research employs a qualitative descriptive method with data taken from selected dialogues and monologues that reflect Othello’s personality. The data were categorized into five dimensions: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. The findings show that Neuroticism (30.77%) is the most dominant trait in Othello’s character, followed by Extraversion (23.08%), Agreeableness (15.38%), Conscientiousness (15.38%), and Openness (15.38%). These traits influence his decisions, relationships, and eventual downfall, indicating that emotional instability and insecurity play a crucial role in the tragic development of the play. This study demonstrates how universal personality traits shape human behavior and conflict in Shakespeare’s drama and shows that modern psychological frameworks can be effectively applied to classical literature.